Obtención de barra de chocolate enriquecida con snack de cáscaras de naranja y mandarina - Mero Cedeño, Eugenia Monserrate (2019)
The objective of this research was to evaluate the enrichment of a chocolate bar incorporating orange peel and tangerine snack. Two types of snack (orange, tangerine) were used at 3, 6 and 9% and a witness (without snack). The experiment was conducted with the DCA and three replicates; the experimental unit was 100 g of chocolate bar. 48 hours after the product was elaborated, the physicochemical characteristics (pH and ºBrix) were analyzed; After 30 days, microbiological (aerobic and moldy) and sensory (smell, taste, texture and acceptance) analyzes were performed. Regarding the physical-chemical results of the chocolate bar, all the treatments complied with the values established in the NTE INEN 621: 2010 statistically it was observed that the 9% orange snack variant obtained the best category. Microbiologically, the statistical trend was maintained with the previous variant; however, it is highlighted that all treatments distance themselves from the control that recorded the highest values of the microbial agents evaluated. In the organoleptic variable, the chocolate bar that received 9% orange peel snack received a favorable acceptance, followed by treatment with 9% tangerine peel snack. It is concluded that the best option to produce chocolate bars is to add orange peel snack at 9% concentration.